Development of Kinesthetic Movement Identification Instruments for Badminton - Sepdanius, Endang; Rifki, Muhamad Sazeli; Gemaini, Andri (Physical Education Theory and Methodology, 2023)
The purpose of this study was to develop an instrument to identify movements and produce recommendations for children who are predicted to be able to develop in badminton. Materials and methods. The kind of this research is research and development consisting of (1) the Preliminary study stage, (2) the Expert validation stage, (3) the Acceptance test stage, and (4) the benefit test stage. The validation stage is carried out by three experts with assessment indicators of suitability, accuracy, convenience, and practicality. The acceptance test phase was obtained from the application of the instrument to the participants. The benefits test stage was determined by a retest test to determine the reliability of the instrument. Participants in the product trial consisted of two groups, namely the male group with 17 participants and the female group with 17 participants. The age of the participants was 6-7 years old. They were elementary school students who were in grade 2. Statistical analysis used a test-retest. Results. The results show that the validation from badminton experts gives an assessment with a presentation of 97% in the very good category, the validation of talent identification experts is 98% in the very good category, and the validation from the coach is 97% in the very good category. For the acceptance test, 4 children (24%) in the first test were recommended, and 5 children (29%) in the second test were recommended. For girls, 2 children (12%) in the first test were recommended, and 3 children (18%) in the second test were recommended. For the reliability test, it was obtained 0.97 in the very strong category for boys and 0.91 in the very strong category for girls. Conclusions. This instrument has been proven valid and reliable and can provide recommendations. The existence of this instrument can facilitate sports teachers and badminton coaches in identifying children's movements.